Long-run Asymmetries in Labor Demand: Estimating Wage Elasticities of Labor Demand Using a Fractional Panel Probit Model - Arnd Kölling (LABOUR, 2019)
Models of labor demand usually use cost or production functions to derive profit-maximizing firm performance. These models often rely on the assumption of symmetrical behavior, i.e., the response to a positive or negative wage shock of the same relative size is identical to the shock, and the estimated labor demand elasticities are the same for increasing and decreasing employment. However, behavioral economics models like loss aversion and endowment effects question the assumption of symmetry in labor demand. In addition, the influence of a labor shortage should be reflected in the investigations. Estimations of Fractional Panel Probit models for three different skill levels are applied to evaluate these findings with a large panel of German establishments. The results indicate asymmetrical structures for long-run own-wage elasticities and for some cross-wage elasticities, putting some doubt on the assumption of strict rationality in labor demand and indicating the influence of labor shortages.
Keywords: 380